2012
DOI: 10.1530/eje-12-0062
|View full text |Cite
|
Sign up to set email alerts
|

Arrest of atherosclerosis progression after interruption of GH replacement in adults with congenital isolated GH deficiency

Abstract: Objective: GH replacement therapy (GHRT) in adult-onset GH deficiency (AOGHD) reduces carotid intima-media thickness (IMT) and increases myocardial mass, with improvement of systolic and diastolic function. These observations have reinforced the use of GHRT on AOGHD. Conversely, we have previously reported that in adults with lifetime congenital and severe isolated GH deficiency (IGHD) due to a mutation in GHRH receptor gene (GHRHR), a 6-month treatment with depot GH increased carotid IMT, caused the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Despite the only modest increase in the levels of IGF-I, GHRT improved lipid profile and body composition, and increased all the parameters related to LV mass, but also increased significantly carotid IMT, and induced the development of carotid atherosclerotic plaques (75). Fortunately, we saw arrrest of the atherosclerosis progression after five years from the interruption of treatment (76). These observations should be considered before starting GHRT in adults with previously untreated congenital GHD.…”
Section: Gh Treatmentmentioning
confidence: 72%
See 1 more Smart Citation
“…Despite the only modest increase in the levels of IGF-I, GHRT improved lipid profile and body composition, and increased all the parameters related to LV mass, but also increased significantly carotid IMT, and induced the development of carotid atherosclerotic plaques (75). Fortunately, we saw arrrest of the atherosclerosis progression after five years from the interruption of treatment (76). These observations should be considered before starting GHRT in adults with previously untreated congenital GHD.…”
Section: Gh Treatmentmentioning
confidence: 72%
“…These features have been published in 42 different publications (2,19,22,25,27,29,30,31,32,33,36,37,38,40,41,44,45,46,47,48,49,50,51,52,53,54,56,57,61,62,63,64,66,67,68,74,75,76,77,78,79,80). We have used this experiment of nature to discover 'usual laws of nature' as suggested by William Harvey, and to understand some aspects of more common conditions such as short stature, insulin resistance, diabetes, atherosclerosis, osteoporosis, cancer and ultimately longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid profile and body composition improved, but carotid intimal thickness increased and carotid atherosclerotic plaques developed within 6 months of treatment, with a 52-fold higher likelihood to have a carotid atherosclerotic plaque by 12 months even after discontinuation of GH therapy. Five years after cessation of GH therapy, intima-media thickness returned to normal, but the number of atherosclerotic plaques did not change (161). Some findings in that model may not be directly applicable to AO-GHD.…”
Section: Information For Reflectionmentioning
confidence: 83%
“…al investigated the bulb IMT in female GH-deficient patients and did not find any significant difference when compared with healthy controls [ 25 ]. GH replacement therapy has in some studies shown beneficial effects on the bulb IMT in individuals with adult-onset GHD [ 23 , 26 , 27 ], but negative effects in congenital GHD [ 28 ]. Thus, data from GHD-patients are conflicting and if anything indicates a negative association between GH and bulb IMT, but data from acromegaly patients support our finding with the association being positive.…”
Section: Discussionmentioning
confidence: 99%